Shared Responsibility After Referral: Ethical Challenges in Preventing Harm - Avny, Ohad; Brezis, Mayer; Tsur, Anat (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2026)
The case illustrates how fragmented communication and blurred accountability between primary and specialty care can compromise the principles of beneficence and nonmaleficence, resulting in preventable harm for patients. To prevent such outcomes, healthcare providers should collaboratively determine who holds primary responsibility for the patient’s care at each stage of the referral process.